Back Cover: Synergy Effect of a π‐Conjugated Ionic Compound: Dual Interfacial Energy Level Regulation and Passivation to Promote Voc and Stability of Planar Perovskite Solar Cells (Angew. Chem. Int. Ed. 11/2022). Issue 11 (11th February 2022) - Liu, Xiaoyuan; Min, Jihyun; Chen, Qian; Liu, Tuo; Qu, Geping; Xie, Pengfei; Xiao, Hui; Liou, Juin‐Jei; Park, Taiho; Xu, Zong‐Xiang
Abstract : Perovskites The π ‐conjugated ionic compound QAPyBF4 was used as a perovskite modulator in the Research Article by Juin‐Jei Liou, Taiho Park, Zong‐Xiang Xu, and co‐workers (e202117303) . Experimental investigations showed that p‐type conjugated cations [QAPy] 2+ adsorb on the perovskite surface with under‐coordinated Pb cations and highly electronegative [BF4 ] − anions enriched at the SnO2 interface. This spontaneous diffusion effect of cation and anion improves the band alignment at two adjacent perovskite interfaces and reduces recombination losses.